2020
DOI: 10.1155/2020/2971827
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Toxic Effect of Biomaterials Coated with Silver Tungstate or Silver Molybdate Microcrystals

Abstract: Purpose. This study evaluated the cytotoxicity of antimicrobial silver tungstate (Ag2WO4) or silver molybdate (Ag2MoO4) microcrystals coating biomaterials. Materials and Methods. The coating procedure was performed onto titanium, zirconia, and acrylic resin specimens. Eluates of the coated specimens were obtained, which were used for cytotoxicity analyses, including Alamar Blue, MTT, and CytoTox-ONE tests. Data were analyzed using two-way ANOVA, followed by the Tukey test (α = 0.05). The results of each experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The cytotoxicity of AgNPs to cell lines was reported to be due to the cellular uptake of nanoparticles through pinocytosis and endocytosis. 47 It has been reported that a cell viability below 50% indicates that NPs are cytotoxic. 48 , 49 The size of the nanoparticles and the plant extract surface coating promoted the cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of AgNPs to cell lines was reported to be due to the cellular uptake of nanoparticles through pinocytosis and endocytosis. 47 It has been reported that a cell viability below 50% indicates that NPs are cytotoxic. 48 , 49 The size of the nanoparticles and the plant extract surface coating promoted the cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Because nanoparticles are taken up by cells by pinocytosis and endocytosis, Silver Nanoparticles have been shown to be harmful to cell lines [45]. According to one investigation, NPs are cytotoxic when cell viability is less than 50% [46].…”
Section: Determination Of Cell Viability By Mtt Assaymentioning
confidence: 99%
“…The plate was supplemented with DMEM and 10 % FBS along with samples dissolved in DMSO (100 mg/mL), diluted further to achieve 1 mg/mL using distilled water to obtain a serial concentrations of 100 μg/mL, 200 μg/mL, 400 μg/mL, 800 μg/mL and aliquots of 10 µL and added later to the microtiter wells of 90 µL of medium and the final active concentration was of 10 μg/mL, 20 μg/mL, 40 μg/mL and 80 μg/mL. The plate was incubated at 37°C with 5% CO 2 , 95% air and 100% RH for 24 h. The plate was read at 570 nm to obtain the absorbance by conversion of MTT to formazan used to calculate the cell growth concentrations using given formula [16][17][18][19]. 3 Results…”
Section: In Vitro Cell Cytotoxicity Studymentioning
confidence: 99%